AKHTᾹ’ YAJIBU AN TUSAHHAHU: AKHTᾹ’ NAHWIYYAH WA USLŪBIYYAH WA IMLᾹIYYAH FI KURRᾹSᾹTIT TADRĪB LI TALABATIL MADRASATIL IBTIDĀIYYAH - Faris Maturedy; Wihdatul Hasanah; Muhammad Alfan (STIQ Amuntai, 2021)
Teaching materials are an important element in the learning process, especially in learning Arabic. These teaching materials can be taken from various learning sources. One of the learning resources that teachers often use is student worksheets. However, there were several errors in the Arabic worksheet entitled